Constitutive notch signaling in adult transgenic mice inhibits bFGF‐induced angiogenesis and blocks ovarian follicle development. Issue 9 (29th May 2014) - Liu, Ju; Deutsch, Urban; Jeong, James; Lobe, Corrinne G.
Summary Notch signaling is important in angiogenesis during embryonic development. However, the embryonic lethal phenotypes of knock‐out and transgenic mice have precluded studies of the role of Notch post‐natally. To develop a mouse model that would bypass the embryonic lethal phenotype and investigate the possible role of Notch signaling in adult vessel growth, we developed transgenic mice with Cre‐conditional expression of the constitutively active intracellular domain of Notch1 (IC‐Notch1). Double transgenic IC‐Notch1/Tie2‐Cre embryos with endothelial specific IC‐Notch1 expression died at embryonic day 9.5. They displayed collapsed and leaky blood vessels and defects in angiogenesis development. A tetracycline‐inducible system was used to express Cre recombinase postnatally in endothelial cells. In adult mice, IC‐Notch1 expression inhibited bFGF‐induced neovascularization and female mice lacked mature ovarian follicles, which may reflect the block in bFGF‐induced angiogenesis required for follicle growth. Our results demonstrate that Notch signaling is important for both embryonic and adult angiogenesis and indicate that the Notch signaling pathway may be a useful target for angiogenic therapies. genesis 52:809–816, 2014. © 2014 Wiley Periodicals, Inc.